Penerapan Teknologi Self-Service Dalam Meningkatkan Customer Satisfaction Pada Usaha Ritel Food and Beverage - Yayuk Arsih; Adhadi Praja; Sandi Perdian; Sugeng Santoso; R. Nurhidajat (Administratif Profesional, 2022)
Digitalization is growing, especially since the COVID-19 pandemic, the industry has been forced to adapt quickly and transform through digital platforms to survive. Various technologies and innovations are present to answer the challenges to continue providing a satisfying shopping experience for customers. One of the digitalization innovations used to serve customer needs in the retail industry is self-service which allows customers to place orders or pay independently. Digital technology is applied to the retail sector for example self-service technology. Business fields that utilize self-service include restaurants, parking lots, gas stations, cinemas, and supermarkets, while the forms of self-service currently available and run by several retailers in Indonesia include Self Order Kiosks, Scan & Go, Scan & Shop, and Click & Collect. This study aims to analyze the application of self-service technology in the food and beverage retail industry and its relationship to increased customer satisfaction. The pre-survey was conducted by distributing questionnaires to customers who are accustomed to making transactions in food & beverage retail by using self-service services. The survey method is given to respondents to get a response to customer satisfaction. Multiple linear regression is used as an analysis and data processing tool to produce R2 of 0.80 which indicates that the completeness of supporting facilities, ease of ordering and payment, speed of service, transaction security, suitability of presentation, care and attention of employees towards customers (X1) and ease of use, visual appearance, product & price information, order efficiency, application response, and the risk of self-service technology (X2) explain customer satisfaction (Y) of 80.16%. It is hoped that the development of self-service technology can provide more detailed information, ease of use, and accuracy of the services offered.